PENGARUH VARIASI WAKTU HOMOGENISASI DENGAN ULTRA TURAX DAN KONSENTRASI SUSU KEDELAI TERHADAP MUTU SUSU SAGA - Abu Amar; Syahril Makosim; Darti Nurani; Louis Eudia; Nur Fajrina (Jurnal Teknologi Industri Pertanian, 2022)
Saga seeds (Adenanthera pavonina, L) contain protein and lignoseric acid and may serve as potentialfunctional food and beverages This study aims to utilize saga seed in producing saga milk with its physical propertysuch as stability and fat globule as well as chemical properties. Soy milk was added to reduce strong beany flavourin saga milk. The saga milk fat globules were reduced by ultraturax or mini homogenizer at 8,000 rpm at differenthomogenization time. A two factorial completely randomized design was carried out with two replications. Sagamilk and soy milk ratio (A): a1 (100 % saga milk); a2 (80 : 20), a3 (75 : 25), and a4 (70 : 30), respectively; andhomogenization time (B) : 0, 10, 20, and 30 minutes (b1, b2, b3, and b4, respectively). Fat globule, protein, andfat contents, fatty acids profile, soluble solids, and pH values were analyzed. Milk flavour compounds wereanalyzed using GCMS. Sensory evaluation was carried out by preference test. The more soymilk added resulted insignificant increase of protein, total soluble solid (p=0.05), significantly reduce size of fat globules and pH value(p=0.05) and also reduced unpleasant flavour. The saga milk was accepted based on sensory evaluation; sagamilk stability was good. Saga milk has dominant content of essential fatty acid including oleic acid, linoleic acidand lignoseric acids. The unpleasant flavor was dominated by hexanal compounds but the typical compounds insaga milk are Dihydroedulan II; Pyrazine, 2-Methoxy-3-Isobutyl, and Benzaldehide-4-Methyl. Formula saga milk:soy milk = 70: 30 is saga milk that is worth producing.Keywords: fat globules, flavor, lignoceric acid, saga milk